Serrated adenomy a karcinomy tlustého střeva - Chlumská, Alena; Martínek, Petr; Mukenšnabl, Petr; Michal, Michael; Zámečník, Michal (Ceskoslovenska patologie, 2016)
Approximately 5 - 35 % of colorectal carcinomas arise through serrated carcinogenesis. The precursor of such carcinomas are serrated adenomas, which differ from conventional adenomas morphologically as well as genetically. Herein, we provide a basic overview of serrated lesions of the large intestine with the focus on histological diagnosis and molecular biology.
Keywords: Carcinoma; adenom; Adenoma; Carcinogenesis; Colonic Neoplasms; karcinom; Colonic Polyps; Humans; polypy tlustého střeva; karcinogeneze; nádory tračníku; lidé; hyperplastic polyp - sessile serrated adenoma - traditional serrated adenoma - serrated carcinoma - serrated carcinogenesis.